STRATEGY FOR DEVELOPING ECONOMIC POTENTIAL IN KERATON VILLAGE SURANENGGALA DISTRICT - Rusdiyana, Rusdiyana; Alfito Martogi Malau (Cirebon International Conference on Education and Economics Proceeding, 2024)
Keraton Village, Suranenggala District, Cirebon Regency, is an area with rural characteristics dependent on the agricultural, livestock, industrial and trade sectors.. To support the success of tasks in Keraton Village requires information and two-way communication, as well as good relationships with all parties, both internal and external. Good village management will produce benefits for the institution, especially in terms of maintaining a good performance image. In this research, it will be analyzed forachieve this goal by using descriptive statistical analysis and qualitative descriptive analysis. With data collection techniques that focus more on frank or covert observation, in-depth interviews and documentation. The sampling technique used in this research is purposive sampling which is used to look for data on village development program strategies, so those who understand the village development strategy best are the village head and his colleagues. Based on the interview results, it can be seen that personal selling is the source of information that is most widely obtained by the public. This was proven by 21 people or 56.8%. Meanwhile, the location factor was the least source of information, namely from 7 people or 18.9%.The results of the analysis show that the entire Keraton Village has potential in the agricultural, livestock, industrial and trade sectors. To optimize the village's potential, revitalizing the role of all existing institutions in the village is very necessary.